COVID-19 vaccine confidence among adults of pima county using the NIMHD minority health and health disparities research framework: A qualitative analysis - Kim Ellis; Pamela Hall; Latrisha Robinson; Sara Ruiz; Maiya G. Block Ngaybe; Christopher Lessenich; Namoonga M. Mantina; Carlos M. Perez-Velez; Beatrice Krauss; Purnima Madhivanan (PLoS ONE, 2026)
Introduction Vaccinations have been established as one of the most effective strategies to prevent the spread of infectious diseases. However, vaccine hesitancy has been a growing issue that needs to be monitored and understood to ensure successful promotion. Historic structural, social, and health disparities have been demonstrated to have significant impact on many health outcomes including vaccination uptake. This study applied the National Institute on Minority Health and Health Disparities Research Framework to examine factors influencing COVID-19 vaccination intention during the COVID-19 pandemic among adults in Pima County, Arizona. Methods Between 22 Aug and 05 Dec 2020, 10 focus group discussions stratified by race/ethnicity, gender and language spoken (FGDs) were conducted virtually among 56 adult residents of Pima County, Arizona. After transcription and translation of FGDs conducted in Spanish, transcripts were organized by demographic characteristics and coded in Dedoose software by four independent coders. The NIMHD Framework’s Domains of Influence were used as a priori codes in the thematic analysis. All participants completed an informed consent process prior to participation. Results Of the 56 participants who took part in the ten focus groups, 27% self-reported being Hispanic or Latinx, 25% were White/non-Hispanic, 9% were Black, and 4% were Asian. The preferred language was most often reported as English. Unique challenges for each demographic group emerged from this analysis, such as language barriers among Hispanic participants, historical mistreatment concerns among Black participants, and conflicting political messages for White participants. Cultural norms, family influences, and attitudes toward autonomy versus community responsibility further shaped vaccine decisions. Effective communication about vaccine safety, clinical trials, and public health messaging were identified as critical to addressing mistrust and vaccine confidence across diverse groups. Conclusion Major themes in this study that predict vaccine intention include health literacy challenges, misinformation, mistrust in healthcare systems, and the desire to protect others. Understanding the behaviors and decisions behind vaccination acceptance and receipt is important for developing effective vaccine communication strategies. Identifying health disparities driving vaccination hesitancy may help guide future strategies and policies to improve vaccination rates, especially among minority groups.